Impact of drug trafficking in young adults from Tamaulipas, Mexico: drugs and insecurity - Gómez San Luis, Anel Hortensia (2016)
This study aimed to understand the experience of young men and women with drug trafficking and the impact on drug use, involvement in criminal groups and insecurity. A case study design was utilized, with a focus group of 10 male and female participants. Results show that violence and insecurity generated by drug trafficking has encouraged the young people to avoid consumption of illegal drugs, or opt for easily accessible drugs to cope with the constant attempts by members of organized crime to recruit them.